Numerical simulation to assess the elastic-strain energy distribution in a silicon rubber disk subjected to a punch shear test (PST) (2016)
Finite element method simulations were implemented to understand how the strain energy is distributed in a disk-like sample during a punch shear test. Material’s Young modulus can be estimated from this test; however, there is not enough available information about the distribution of the strain energy inside the sample during the deformation process. The proposed methodology seeks to give insight into the deformation process. Experimental results for a cured silicon rubber sample were used to validate the simulation results. It was found that the estimation of the Young modulus with the punch shear test depends on the ratio between the span-to-punch diameters. This conclusion applies to the simulated results, following Timoshenko’s theory for the deformation of thin plates. Understanding how energy is accumulated during a punch shear test is an important and useful characteristic in terms of the design of armor systems.